Evidence of Peste des petits Ruminants’ Virus in Dromedary Camels in the Kingdom of Saudi Arabia between 2014 and 2016 - Maged Gomaa Hemida; Hussain Mohammed Al-Ghadeer (Veterinary Medicine International)
Infection with the Peste des petits ruminants virus (PPRV) is a highly devastating viral infection of small ruminants. Dromedary camels live in close proximity of small ruminants in Arabian Peninsula (AP) and many other regions in the world. Little is known about the reasons behind continuous PPRV emergence in Saudi Arabia (KSA). Our objective was to test some dromedary camel population across the kingdom for the presence of specific PPRV antibodies. Our results show detection of specific PPRV antibodies (2.92%) in sera of tested dromedary camels from the eastern and south regions of the KSA. Our results suggest the exposure of dromedary camels to PPRV infection. Thus, dromedary camels may play some important roles in the sustainability of PPRV in the small ruminants across the AP. This is the first study examined the nationwide prevalence of the PPRV in dromedary camels in the KSA.